Environmental Tobacco Smoke in Designated Smoking Areas in the Hospitality Industry: Exposure Measurement, Exposure Modelling & Policy Assessment - MCNABOLA, AONGHUS (My University, 2012)
Tobacco control policy has been enacted in many jurisdictions worldwide banning smoking in the workplace. In the hospitality sector many businesses such as bars, hotels and restaurants have installed designated smoking areas on their premises and allowance for such smoking areas has been made in the tobacco control legislation of many countries. An investigation was carried out into the level of exposure to ETS present in 8 pubs in Ireland which included designated smoking areas complying with two different definitions of a smoking area set out in Irish legislation. In addition, ETS exposure in a pub with a designated smoking area not in compliance with the legislation was also investigated. The results of this investigation showed that the two differing definitions of a smoking area present in pubs produced similar concentrations of benzene within smoking areas (5.1-5.4?g/m3) but differing concentrations within the `smoke-free? areas (1.42-3.01?g/m3). Smoking areas in breach of legislative definitions were found to produce the highest levels of benzene in the smoking area (49.5?g/m3) and `smoke-free? area (7.68?g/m3). 3D exposure modelling of hypothetical smoking areas showed that a wide range of ETS exposure concentrations were possible in smoking areas with the same floor area and same smoking rate but differing height to width and length to width ratios. The results of this investigation demonstrate that significant scope for improvement of ETS exposure concentrations in pubs and in smoking areas may exist by refining and improving the legislative definitions of smoking areas in law.
PUBLISHED
Keywords: ETS; Smoking; Benzene.; Personal Exposure; Tobacco Control; Smoking Areas; Inclusive Society; Smart & Sustainable Planet